The microrna deregulation in Colorectal Cancer / Yong Fung Lin - Yong, Fung Lin (2014)

(untitled)
Colorectal cancer (CRC) is the carcinoma of the colon and rectum in the gastrointestinal system. CRC is the third most common cancer in men and the second in women worldwide. The limitations of the currently available biomarkers and technologies for CRC screening and surveillance have highlighted the necessity of finding novel biomarkers. Recently, microRNA (miRNA)-based studies have rendered remarkable contribution in the elucidation of mechanisms of carcinogenesis. miRNAs are short, non-coding RNA molecules that act as regulators of gene expression through messenger RNA (mRNA) degradation or translational inhibition. Blood miRNA expression profiles offer great potential as non-invasive biomarkers. In the present study, the aims were to characterise and correlate the tissue and blood miRNA expression patterns of primary CRC patients, and establish the functional roles of the identified miRNAs in the carcinogenesis of CRC. Firstly, the miRNA profiling study was divided into two phases: (I) marker discovery by miRNA microarray using paired cancer tissues (n = 30) and blood samples (CRC, n = 42; control, n = 18); (II) marker validation by reverse transcription-quantitative real-time polymerase chain reaction (RT-qPCR) using an independent set of paired cancer tissues (n = 30) and blood samples (CRC, n = 70; control, n = 32). Logistic regression and receiver operating characteristic curve analyses were applied to obtain diagnostic utility of the miRNAs. Seven miRNAs (miR-150, miR-193a-3p, miR-23a, miR-23b, miR-338-5p, miR-342-3p and miR-483-3p) were found to be differentially expressed in both tissue and blood samples. Significant positive correlations were observed in the tissue and blood levels of miR-193a-3p, miR- 23a and miR-338-5p. These miRNAs were demonstrated as a classifier for CRC detection, with a receiver operating characteristic curve area of 0.887 (80.0% sensitivity, 84.4% specificity and 83.3% accuracy). Next, these miRNAs were subjected to functional and miRNA:mRNA target validation studies via miRNA mimics and iv inhibitors transfections. SW480 and SW620 CRC cell lines were utilised. Cell viability, apoptosis, migration and invasion assays were conducted. Luciferase assays were performed for the validation of target mRNAs. The expression levels of target mRNAs and proteins in clinical CRC samples and cell lines were assessed using RT-qPCR and Western blot. miR-193a-3p was identified to be involved in CRC cell migration and invasion by targeting FOXO4. miR-23a was determined to possess apoptosis resistance function by targeting APAF1. However, the transfection of miR-338-5p did not reveal significant findings in the cell viability, apoptosis, migration and invasion analyses. In conclusion, miRNA deregulation in the blood is reflective of that in the CRC tissue. The triple miRNA classifier of miR-193a-3p, miR-23a and miR-338-5p may serve as potential blood biomarkers for CRC detection. The miRNA:mRNA target validation studies have highlighted the potential application of miR-193a-3p:FOXO4 and miR- 23a:APAF1 regulation axes in miRNA-based therapy and prognostication.